Pengaruh Terapi Massage Effleurage Terhadap Nyeri Pinggang Pada Ibu Inpartu Kala I di Ruangan Poned Puskesmas Adipala 1 - Elvia Hetika Sari; Tri Aksari, Septi; Didik Nur Imanah, Norif; Sya’baniah Khomsah, Yuli (An-Najat, 2025)
Effleurage massage, a gentle and continuous non-pharmacological massage technique, works based on the gate control theory to reduce pain by blocking pain signals and stimulating endorphin production. This qualitative case study was conducted on Mrs. U, a 30-year-oldwoman at 39 weeks 2 days of pregnancy. The study aimed to evaluate the effect of effleurage massage therapy on labor pain intensity during the first stage of labor. Labor pain often peaks duringthis stage, potentially triggeringanxiety, increasing adrenalinelevels, andreducingblood flow to the fetus. Unmanaged pain may lead to a negative and traumatic childbirth experience. Beforetheeffleuragemassage,Mrs.U’s pain scalewas 8 (severepain).After1 hour ofeffleurage massage applied to the lower back, the pain scale decreased to 4 (moderate pain). These results indicate that effleurage massage is effective in reducing labor pain during the first stage, enhancing maternal comfort, and can be applied as a simple and safe non-pharmacological intervention in healthcare settings.